CONSTITUTIONAL COURTS AND JUDICIAL REVIEW: LESSON LEARNED FOR INDONESIA (MAHKAMAH KONSTITUSI DAN PENGUJIAN UNDANG-UNDANG: PEMBELAJARAN BAGI INDONESIA) - Muhammad Siddiq Armia (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2017)
In the context of reviewing law through judiciary organ, the court plays significant role to review several regulation. This article specifically will discuss regarding the role of court on judicial review. This idea spreads out worldwide including in Indonesia. The Constitutional court and judicial review are two words which having inextricably meaning that attached to each other. On worldwide, the system of reviewing law by involving judges commonly has been practiced by several countries. There are two most significant state organs that plays role in the system, they are constitutional court and supreme court. Most countries do not have constitutional court and will deliver the authority of judicial review through supreme court. It has added more tasks, not only to adjudicate the common case, but also regarding constitutionality matter of an act against constitution. This model is commonly known as a centralized model, as practiced in the United State of America. In the Countries that owned a constitutional court, will certainly deliver the authority of judicial review through constitutional court. 108 NEGARA HUKUM: Vol. 8, No. 1, Juni 2017 This model is commonly known as Kelsenian’s model. In this model, the constitutional court will merely focus on the constitutionality of regulations, and ensuring those regulations not in contradicting with the constitution. The Supreme Court in this model merely focus on handling common cases instead of regulations. Those two model of judicial review (through the constitutional court and the supreme court) has widely been implemented in the world legal systems, including in Indonesia. In the authoritarian regime, Indonesia implemented the centralized model, which positioned the Supreme Court as the single state organ to handle the common case and also judicial review. Having difficulties with the centralized model, after the constitution amendment in 2003, Indonesia has officially formed the constitutional court as the guardian of constitution. However, the Indonesian Constitutional Court (ICC) merely examine and/or review the statute that against the Indonesian’s Constitution year 1945, and related to the legislations products lower than the statute will remains the portion of the Supreme Court jurisdiction. Such modification is vulnerable resulting a judgement conflict between the ICC and the Supreme Court.ABSTRAKPosisi peradilan memainkan peranan penting dalam proses uji materi undang-undang. Mahkamah konstitusi dan pengujian undang-undang merupakan dua kata yang saling berkaitan memiliki keterikatan. Ide dasar pengujian peraturan perundang-undangan melalui lembaga peradilan berkembang luas di dunia hingga sampai ke Indonesia. Sistem pengujian undang-undang dengan melibatkan hakim sudah sering digunakan dan dipraktekkan di berbagai negara. Terdapat dua organ kenegaraan yang mempunyai peran vital dalam memaikan peran ini yaitu mahkamah konstitusi dan mahkamah agung. Model seperti ini lebih dikenal dengan model terpusat di suatu lembaga negara sebagaimana yang di Amerika Serikat. Sedangkan negara yang mempunyai mahkamah konstitusi akan melimpahkan kewenangan pengujian undang-undang kepada mahkamah konstitusi, model ini dikenal dengan model Kelsen. Pada model ini mahkamah konstitusi hanya berfokus pada konstitutionalitas peraturan peraturan perundang-undangan serta memastikannya agar tidak bertentangan dengan norma dalam konstitusi. Mahkamah agung pada model ini hanya berfokus untuk menangani kasus sehari-hari saja, bukan untuk menguji peraturan perundang-undangan. Dua model ini pengujian undang-undang ini (melalui mahkamah konstitusi dan mahkamah agung) sering diterapkan dalam sistem ketatanegaraan dunia, termasuk juga di Indonesia. Pada zaman rezim otoriter, Indonesia menerapkan sistem pengujian undang-undang terpusat, dengan memposisikan Mahkamah Agung sebagai organ tunggal negara yang menangani perkara sehari-hari dan pengujian undang-undang. Menemukan hambatan dengan model terpusat ini, akhirnya Indonesia membentuk Mahkamah Konstitusi. Mahkamah Konstitusi Indonesia hanya menguji undang-undang terhadap Undang-Undang Dasar 1945. Sedangkan peraturan perundangundangan di bawah undang-undang tetap menjadi kewenangan Mahkamah Agung. Modifikasi seperti ini berakibat rentannya terjadi pertentangan putusan antara Mahkamah Konstitusi dan Mahkamah Agung.